2015
DOI: 10.1017/langcog.2015.19
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Linguistics and interactional discourse: time to enter into dialogue

Abstract: Usage-based theories hold that the sole resource for language users’ linguistic systems is language use (Barlow & Kemmer, 2000; Langacker, 1988; Tomasello, 1999, 2003). Researchers working in the usage-based paradigm, which is often equated with cognitive-functional linguistics (e.g., Ibbotson, 2013, Tomasello, 2003), seem to widely agree that the primary setting for language use is interaction, with spontaneous face-to-face interaction playing a primordial role (e.g., Bybee, 2010; Clark, 1996; Geeraerts &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Another open question concerns the relation between extravagance and other, partly overlapping concepts such as expressivity and evaluativity (see footnote 1 above), all of which relate to pragmatic and interpersonal dimensions of linguistic constructions. Given the "interactional turn" in many areas of usage-based linguistics, including Cognitive Linguistics and Construction Grammar (see Zima & Brône 2015), these often neglected dimensions have recently come to the centre of attention in constructionist approaches. While previous work has convincingly shown that they can contribute to explanatory accounts of language variation and change, there is still some conceptual and terminological groundwork to be done, and we hope that the present paper can serve as a first stepping stone towards that goal.…”
Section: Resultsmentioning
confidence: 99%
“…Another open question concerns the relation between extravagance and other, partly overlapping concepts such as expressivity and evaluativity (see footnote 1 above), all of which relate to pragmatic and interpersonal dimensions of linguistic constructions. Given the "interactional turn" in many areas of usage-based linguistics, including Cognitive Linguistics and Construction Grammar (see Zima & Brône 2015), these often neglected dimensions have recently come to the centre of attention in constructionist approaches. While previous work has convincingly shown that they can contribute to explanatory accounts of language variation and change, there is still some conceptual and terminological groundwork to be done, and we hope that the present paper can serve as a first stepping stone towards that goal.…”
Section: Resultsmentioning
confidence: 99%
“…This 'dialogic turn combines insights from usage-based linguistics, conversation analysis and interactional pragmatics, and it has been formalised in the so-called dialogic syntax paradigm (cf. ; see also Zima & Brône 2015;Tantucci et al 2018). The aim of dialogic syntax is to cast new light on both the formal and the pragmatic encoding of meaning as an adaptive mechanism unfolding through dialogic engagement, viz.…”
Section: Resonance and Dialogic Engagementmentioning
confidence: 99%
“…For this book, there is a beginning with the introduction to the dialogic turn in cognitive linguistic studies, discussed in chapter 1. As a term originating from "interactional turn" intending to yield dynamic perspectives in examining discourse and interactional language, 'dialogic turn' unveils the view that intersubjectivity in interpersonal interaction among humans ought to be probed in the construction of paired utterances (Zima and Brône, 2015;Zeng, 2018).…”
Section: A Brief Review Of the Application Of Dialogic Construction Grammar Theorymentioning
confidence: 99%